Layer-4 Load Balancer for Flow Size Prediction with TCP/UDP Separation Using P4 - Hussein, Sanaa Alaa; Salman, Mustafa Ismael (Iraqi Journal of Science, 2021)
Nowadays, datacenters become more complicated and handle many more users’ requests. Custom protocols are becoming more demanded, and an advanced load balancer to distribute the requests among servers is essential to serve the users quickly and efficiently. P4 introduced a new way to manipulate all packet headers. Therefore, by making use of the P4 ability to decapsulate the transport layer header, a new algorithm of load balancing is proposed. The algorithm has three main parts. First, a TCP/UDP separation is used to separate the flows based on the network layer information about the used protocol in the transport layer. Second, a flow size prediction technique is adopted, which relies on the service port number of the transport layer. Lastly, a probing system is considered to detect and solve the failure of the link and server. The proposed load balancer enhances response time of both resources usage and packet processing of the datacenter. Also, our load balancer improves link failure detection by developing a custom probing protocol.